The Effect Of Fuel Made From Waste Cane To Boiler Efficiency - Erland G (Bandar Lampung University (UBL), 2017)
Boiler or Boiler is a tool that has a function to heat the water up into the highpressure steam. In the industrial boiler is the main engine that plays a very important, because the steam boiler proceeds will be used for the needs of the production process of a factory. Boiler used in PG. Bungamayang is a boiler with a water pipe fuel types bagasse. These boilers operate with a maximum pressure of 25kg / cm 2 and a maximum steam generating as much as 25 tons / hour. To calculate the efficiency of a boiler can use the direct method is energy obtained from the working fluid thanℎthe-ℎ energy contained in thefuelboiler 100% boiler efficiency rate can be caused by good or bad of the boiler fuel. In this final duty fuel used is bagasse, there is the content Results Purity (HK) end mill juice. Optimal boiler efficiency at PG. Bungamayang of 77% based on the calculation and the results of the analysis of the percentage of HK sap mill end of the fuel bagasse is 33%, but if HK sap in the fuel is rising to 46%, the efficiency of the boiler will decrease to 40%. So it can be said that if HK sap end mill bagasse fuel in the percentage is too high then the efficiency of the boiler will be very small, and causes the plant performance is not optimal. The incident occurred as HK roomie is a divisor of the percentage of sugar and non-sugar. The higher the percentage of HK sap, meaning the bagasse contains a lot of sugar content